IMPACT OF NATIONAL AGRICULTURAL INSURANCE SCHEME (NAIS) ON RICE FARMING IN MAHABOOBNAGAR DISTRICT OF TELANGANA - M.H.V. BHAVE, U. HARI KRISHNA, R. VIJAYA KUMARI, K. SUHASINI and (The Journal of Research, PJTSAU, 2019)
The idea of crop insurance in India was conceptualized as far back as 1920, when S. Chakravarti proposed an agricultural insurance scheme based on rainfall approach (Vyas and Singh, 2006). In 1979, with the recommendations of Dhandekar Committee, the General Insurance Corporation implemented the Pilot Crop Insurance Scheme based on homogenous area approach. Following this, another scheme called ‘Comprehensive Crop Insurance Scheme (CCIS)’ was implemented in 1985. This scheme was further modified and implemented throughout the country as National Agricultural Insurance Scheme (NAIS) in 1999. Agriculture Insurance Company of India Ltd. (AICL) has been managing and implementing this crop insurance scheme in India since April 2003. Unlike earlier insurance schemes which were restricted to the loanee farmers only, NAIS is available to both loanee and non-loanee farmers. Against this background it was felt that there is need to study the impact of NAIS. Further, it is presumed that there would be significant difference in productivity and input use on rice farms.